Pengembangan Teknik Dasar Menggunakan Video Tutorial Pada Atlet Pelajar Ekstrakurikuler Olahraga Gulat - Sabaruddin Yunis Bangun; Gery Ginting (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
The purpose of this study was to develop basic techniques using video tutorials for extracurricular student athletes in wrestling. The method in this study uses research and development (R&D). The population in this study were extracurricular student athletes in wrestling, a sample of 24 people, 10 samples were carried out in product trials and 14 samples were carried out in use trials. Data collection techniques using questionnaires or questionnaires. Data analysis technique using quantitative data analysis percentage and Likert scale. The results of the study were: From the results of the sports material validator it was found that the overall percentage was 81% with a